Coisalidade, transfiguração e antítese em objetos artístico-educacionais - Rattes, Luah Souza Caribé [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The research deals with the educational potential of the objects of our daily lives, from their immediate existence, which reflects interests and formats of capital and dominant ideologies, to the extent that it educates silently and constantly, as Mészáros notes in his book “Education beyond capital”, to compliance with certain rules of social conduct, to its potential as raw material for the production of works of art, as they go through a process of “transfiguration”, as addressed by Arthur C. Danto in “The Transfiguration of the Common Place”. The idea that triggers in this work is to unite plastic production and research in art-education, working with the Educational Research Based on Art, and as a principle of the concerns to be worked on we chose to bring as an example the costura-coleta workshop, taught at SESC Pompeia during the internship held at the exhibition Afonso Tostes: Floresta D’Água, in 2019. The development of the workshop was linked to a process of research and creation on mediation in exhibitions, as part of the continued training of the art-educator, and that followed the path of the development of an authorial workshop in direct relation to the issues raised in the exhibition and at the same time with the artistic production that had been developed.

A pesquisa trata do potencial educativo dos objetos do nosso cotidiano, desde sua existência imediata, que reflete interesses e formatos do capital e das ideologias dominantes, na medida em que educa silenciosa e constantemente, como observa Mészáros em seu livro “A educação para além do capital”, à conformidade com certas regras de conduta sociais, até o seu potencial como matéria prima para a produção de obras de arte, ao passarem por um processo de “transfiguração”, como abordado por Arthur C. Danto em “A Transfiguração do Lugar Comum”. A ideia que desencadeia neste trabalho é unir a produção plástica e a pesquisa em arte-educação, trabalhando com a Pesquisa Educacional Baseada em Arte, e como princípio das inquietações a serem trabalhadas optou-se por trazer como exemplo a oficina Costura-Coleta, ministrada no SESC Pompeia durante o estágio realizado na exposição Afonso Tostes: Floresta D’Água, em 2019. O desenvolvimento da oficina esteve vinculado a um processo de investigação e criação sobre mediação em exposições, como parte da formação continuada do arte- educador, e que seguiu o caminho do desenvolvimento de oficina autoral em relação direta com as questões suscitadas na exposição e ao mesmo tempo com a produção artística que vinha sendo desenvolvida.
Thingness, transfiguration and anthitesis in artistic-educacional objects
Keywords: Arte contemporânea; Cultura visual; Arte-educação; Transfiguração; Coisalidade; Objeto mediador